Development and Validation of RP-HPLC Method for Oral Printed Films of Ketorolac Tromethamine - Dule, Priya; Kilor, Vaishali (Asian Journal of Pharmaceutical Research and Development, 2022)
For the analysis of Ketorolac Tromethamine in Oral film formulation, a simple, precise, and accurate method was developed and validated. On a Kromosil C18 column (150 cm 4.6 mm 5), an isocratic HPLC analysis was performed. The chemical was isolated using a solution of A 55:45 V/V methanol and ammonium dihydrogen phosphate buffer with a pH of 3.0 was used. Adjusted with 1.5 mL/min flow of O-phosphoric acid as the mobile phase UV detection was carried out. Photo diode array detection was used at 314 nm. The retention time was discovered to be 6.08 minutes. The system suitability criteria, such as theoretical plate count, tailing, and percentage, should be kept to a minimum. The RSD between six standard injections was within the acceptable range. The procedure was tested and found to be valid. According to the ICH guidelines over the concentration range of 50-150 gm/L, calibrations were linear. The correlation coefficient (r) of 0.999 indicates this. The method’s resilience was tested by systematically changing the chromatographic settings. The approach described may be used for routine quantitative analysis.